2005
DOI: 10.1007/s00213-005-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

A selective test for antidepressant treatments using rats bred for stress-induced reduction of motor activity in the swim test

Abstract: These results suggest that the procedure described here, which uses a rat subject that has been bred for vulnerability to stressful conditions, may be a selective screening technique for effective antidepressant treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 35 publications
(42 reference statements)
1
18
0
1
Order By: Relevance
“…data). Nevertheless, the effectiveness of antidepressants in reducing immobility and enhancing active behaviours in male and female animals depends on the compound and the selected dosage scheme (Barros and Ferigolo, 1998;Contreras et al, 1998;Consoli et al, 2005;West and Weiss, 2005;Kokras et al, 2009a;Pitychoutis et al, 2011; Allen et al, 2012;Dalla et al, 2012;Flores-Serrano et al, 2013). For instance, with the use of the modified FST, sertraline enhances swimming duration in both sexes , and this has been linked with changes in 5-hydroxytryptaminergic activity (Detke et al, 1995;Detke and Lucki, 1996;Mikail et al, 2012).…”
Section: Sex Differences In Animal Models Of Depressionmentioning
confidence: 99%
“…data). Nevertheless, the effectiveness of antidepressants in reducing immobility and enhancing active behaviours in male and female animals depends on the compound and the selected dosage scheme (Barros and Ferigolo, 1998;Contreras et al, 1998;Consoli et al, 2005;West and Weiss, 2005;Kokras et al, 2009a;Pitychoutis et al, 2011; Allen et al, 2012;Dalla et al, 2012;Flores-Serrano et al, 2013). For instance, with the use of the modified FST, sertraline enhances swimming duration in both sexes , and this has been linked with changes in 5-hydroxytryptaminergic activity (Detke et al, 1995;Detke and Lucki, 1996;Mikail et al, 2012).…”
Section: Sex Differences In Animal Models Of Depressionmentioning
confidence: 99%
“…Depression-Ample evidence indicates that, in addition to affecting anxiety-related behavior, Avp affects depression-related behavior. In rodents, the forced swim task produces immobility that can be countered with antidepressants (Porsolt et al, 1977;West and Weiss, 2005). Acute forced swimming induces a significant increase in Avp release in both the SON and PVN that increases further in the PVN with repeated swimming .…”
Section: 42mentioning
confidence: 99%
“…Efficacy data for newly included studies were calculated using the same method reported in Cahill et al 15 -based on the numbers of people randomised to an intervention and excluding any deaths or untraceable moves in accordance with the Russell Standard. 31 Drop-outs or those patients lost to follow-up are treated as continuing smokers. It is beyond the scope of this short report to conduct a systematic review of adverse events for varenicline and cytisine, taking into account long-term observational studies.…”
Section: Data Extractionmentioning
confidence: 99%